The Validity of Clues is Practical on Human Sensory Materials to Improve the Critical Thought Skills of Learners - Sari, Martika Arisma; Wulandari, Tabitha (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2025)
The primary purpose of this study is to describe the design and validity of the teaching material of electronic practice through problem-based learning (PBL) to improve critical thinking skills. The type of research used is development or research and development (R&D) using the 4D development design by Thiagarajan (1974). The research subject researchers use as the validator expert is the lecturer and biology teacher of SMAN 3 Tuban. Research and development data collecting that researchers use is a validation sheet. The research data analysis USES descriptive and verifiable techniques from the study. The results show the validity of the electronic practical instructions in terms of content/material worthiness achieves an average of 80% in valid categories, terms of systemic worthiness achieve an average of 82% in valid categories, terms of language worthiness achieves an average of 80% valid categories, and in terms of eligibility scores an average of 77% valid categories. The overall validity score of the electronic practical clue developed by 79.75% valid categories.